Clinical Application of Arterial Spin-Labeling MR Imaging in Patients with Carotid Stenosis: Quantitative Comparative Study with Single-Photon Emission CT - Uchihashi, Y.; Hosoda, K.; Zimine, I.; Fujita, A.; Fujii, M.; Sugimura, K.; Kohmura, E. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Arterial spin-labeling is an emerging technique for noninvasive measurement of cerebral perfusion, but concerns remain regarding the reliability of CBF quantification and clinical applications. Recently, an ASL implementation called QUASAR was proposed, and it was shown to have good reproducibility of CBF assessment in healthy volunteers. This study aimed to determine the utility of QUASAR for CBF assessment in patients with cerebrovascular diseases. MATERIALS AND METHODS: Twenty patients with carotid stenosis underwent CBF quantification by ASL (QUASAR) within 3 days of performance of 123I-iodoamphetamine-SPECT. CVR to acetazolamide also was assessed by ASL and SPECT. In surgically treated patients, the respective scans before and after the procedures were compared. RESULTS: Regional CBF and CVR values measured by ASL were significantly correlated and agreed with those measured by SPECT (rs = 0.92 and 0.88, respectively). A Bland-Altman plot demonstrated good agreement between 2 methods in terms of CBF quantification. Furthermore, ASL could detect pathologic states such as hypoperfusion, impaired vasoreactivity, and postoperative hyperperfusion, equivalent to SPECT. However, ASL tended to overestimate CBF values especially in high-perfusion regions. CONCLUSIONS: ASL perfusion MR imaging is clinically applicable and can be an alternative method for CBF assessment in patients with cerebrovascular diseases. ACZacetazolamideAIFarterial input functionASLarterial spin labelingCAScarotid artery stentingCBFcerebral blood flowCEAcarotid endarterectomyCVRcerebral vasoreactivityIMPiodine 123 N-isopropy-p-iodoamphetamineNASCETNorth American Symptomatic Carotid Endarterectomy TrialPETpositron-emission tomographyQUASARquantitative STAR labeling of arterial regionsROCreceiver operating characteristicROIregion of interestSPECTsingle-photon emission CTlVencvelocity encoding